Evangelische protestanten in tijden van secularisering - Kregting, Joris; Wijma, Merijn (Religie & Samenleving, 2023)
The Netherlands is a forerunner in the process of secularization. However, high quality data on whether this also applies to small groups of Protestants hardly exist. This article uses two surveys, administrated in 1988 and 2020 with over 1000 respondents each, to describe how evangelical Protestants relate to the process of secularization. In 2020, evangelical Protestants are still very loyal to their church and faith but less so than a few decades ago and young evangelicals less so than the elderly. In addition, norms and values related to their faith have become more liberal over time, especially with regard to relationships and sexuality.